2012
DOI: 10.1063/1.4737922
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability aspects and optimization of linseed biodiesel blends for compression ignition engine

Abstract: The present work is aimed at experimental optimization of the linseed biodiesel blends as sustainable fuel for compression ignition engine. The experiments were conducted to study the comparative combustion, performance, and emissions characteristics of linseed biodiesel-diesel fuelled single cylinder compression ignition engine. The comparison was done with base fuel as diesel and linseed oil biodiesel at 1500 6 10 rpm. Experiments were performed at various blends of linseed biodiesel and engine loads. At ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Murthy [160] analysed the performance of tobacco oil based biodiesel in a single-cylinder direct injection engine and observed a remarkable decrease in NO x emissions compared to pure diesel fuel. Jindal and Salvi [125] reported that by using linseed oil blends, the emission of CO and hydrocarbon and opacity were reduced but there was slight increase in CO 2 and NO emissions. Enweremadu et al [161] carried out a series of experiments on shea butter methyl ester and found that the NO x emissions increased with increase in biodiesel content in the fuel blends while the emissions of CO, HC and smoke opacity decreased.…”
Section: Engine Emission Parametersmentioning
confidence: 96%
See 1 more Smart Citation
“…Murthy [160] analysed the performance of tobacco oil based biodiesel in a single-cylinder direct injection engine and observed a remarkable decrease in NO x emissions compared to pure diesel fuel. Jindal and Salvi [125] reported that by using linseed oil blends, the emission of CO and hydrocarbon and opacity were reduced but there was slight increase in CO 2 and NO emissions. Enweremadu et al [161] carried out a series of experiments on shea butter methyl ester and found that the NO x emissions increased with increase in biodiesel content in the fuel blends while the emissions of CO, HC and smoke opacity decreased.…”
Section: Engine Emission Parametersmentioning
confidence: 96%
“…Parlak et al [124] investigated the effects of steam injection on performance and emissions of a diesel engine fuelled with tobacco seed oil methyl ester and found that steam injection into the engine fuelled with B20 fuel improved torque, effective power, effective efficiency and BSFC. Jindal and Salvi [125] reported that at full load, blends with 10% of linseed oil (B10) give higher indicated thermal efficiency (10% to 12%) and lower specific fuel consumption (4% to 6%) compared to pure diesel fuel.…”
Section: Engine Performance Parametersmentioning
confidence: 99%
“…The generated hydrogen can be used for power generation or process heating in the industry itself, making more viable and economical option. The integrated processes combine normally distinct technologies, using wastes from one process as feed for another to increase overall process efficiency [40,41]. For example, the municipal solid waste (MSW) gasification for generation of hydrogen [42], corn distillery waste water as source of organic carbon for bio-hydrogen production, etc.…”
Section: Hydrogen Production From Renewable Energy Sourcesmentioning
confidence: 99%
“…Research is now being focused to find the optimum combination of input variables in terms of performance and emission characteristics. Few Authors have reported the optimum values of responses in diesel engines, Bunce et al, 5 Ganapathy et al, 12 Jindal and Salvi, Maheshwari et al, Balajiganesh and Reddy, and Karuppasamy et al [14][15][16][17] There are various tools available for optimization of engine performance and emission parameters such as Response surface methodology (RSM) based on Central composite rotatable design (CCRD), Artificial neural network (ANN), Genetic algorithm (GA), fuzzy logic, etc. But till date no work has been reported for predicting optimum performance and emission parameters at particular input variables of mahua biodiesel.…”
mentioning
confidence: 99%